The Influence of Hotel Chain Logistics on Customer Loyalty: A Case Study in the Chinese Hospitality Sector - Yu, Deshun; Rojniruttikul, Nuttawut (My University, 2025)
This study investigates the factors influencing customer loyalty within the Chinese hospitality sector, focusing on brand image, logistics communication channels, sustainability practices, transportation accessibility, and service quality. Data were collected from 385 customers with recent experiences in chain-operated hotels across various regions in China. A structured questionnaire facilitated the collection of quantitative data, which were analyzed using multiple linear regression. The results reveal statistically significant positive effects of brand image, logistics communication channels, sustainability practices, and transportation accessibility on customer loyalty. However, service quality did not demonstrate a statistically significant impact. The regression model accounts for a substantial proportion of the variance in customer loyalty, as indicated by a high R-square value (R2 = 0.850). These findings underscore the importance of strategically managing these factors to enhance customer loyalty within hotel chains. While the results are specific to the Chinese hospitality industry, the core principles identified—such as the significance of brand image and logistics communication—are likely applicable to other countries and sectors. However, cultural, economic, and industry-specific factors should be considered when generalizing these findings to different contexts. This study contributes to the existing literature by providing empirical evidence on the drivers of customer loyalty in the Chinese hospitality industry and offers actionable insights for hotel chains looking to enhance their competitiveness and foster long-term customer relationships. Future research is encouraged to explore these dynamics in different cultural and industrial settings to assess the broader applicability of these results.
Keywords: Brand image; Customer loyalty; Hospitality sector; Service quality